Pathophysiological Effect of Enlarged Adenoid on Middle Ear in Children (Bangladesh Journal of Otorhinolaryngology, 2023)
Objective: To identify the incidence of otitis media with effusion (OME) in children with enlarged adenoid.Methodology: This is a cross sectional observational study was carried out at Department of Otolaryngology and Head Neck surgery of Sir Salimullah Medical College Mitford Hospital, Dhaka from July 2014 to June 2016. One Hundred and Fifty (150) children with enlarged adenoid were included in this study. All patients were subjected for history, local physical examination, evaluation of adenoid size by X ray of nasopharynx lateral view. Pure tone audiometry & tympanometry were done in all patients. Informations were recorded in a specially designed data collection sheet.Result: Among 150 children with enlarged adenoid 30(20%) patient had OME, majority of patients (60%) were age group 7-9 years. Male were predominant (60%) than female (40%). Among 150 patients grade- I was 16%, grade II- was 26%, grade-III was 54% and grade IV was 4%.According to the grading of enlarged adenoid cases , grade I, grade II , grade III and grade IV had 8.33%,15.38% ,23.46% and 50% cases had OME respectively. Hearing loss was in 33(22%) children. According to tympanometry, type A curve was in 118(78.67%) children, type B 26(17.33%) and type C 6(4%) children.Conclusion: Enlarged adenoid is associated with otitis media with effusion. Incidence of Otitis media with effusion increases with the proportion of severity of nasopharyngeal obstruction by enlarged adenoid.Bangladesh J Otorhinolaryngol 2023; 29(1): 11-16